1977
DOI: 10.1111/j.1467-8624.1977.tb03976.x
|View full text |Cite
|
Sign up to set email alerts
|

Toys and Social Interaction between Infant Peers

Abstract: Claims that young infants fail to react in a social manner to one another and that toys preempt attention to peers were assessed by comparing the interactions observed between infant peers when they met in the presence of toys versus in their absence. 44 pairs of unacquainted infants (either 10--12 or 22--24 months of age) came with their mothers to an unfamiliar room. Without toys available in the room, infants of both ages more often contacted one another, smiled at and gestured to one another, and duplicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
2
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 6 publications
1
18
2
1
Order By: Relevance
“…When the 2-yearolds did respond to peers in the current study, their responses were situationally con tingent, with few being redundant or noncon tingent to the previous message. The lack of redundant responses (imitative responses) differs from the work of Eckerman and Whatley [1977] and Eckerman and Stein [1982]. It is not surprising that the younger toddlers in Eckerman and Whatley's [1977] study depended on imitative responses.…”
Section: -Year-old Dyadscontrasting
confidence: 50%
See 3 more Smart Citations
“…When the 2-yearolds did respond to peers in the current study, their responses were situationally con tingent, with few being redundant or noncon tingent to the previous message. The lack of redundant responses (imitative responses) differs from the work of Eckerman and Whatley [1977] and Eckerman and Stein [1982]. It is not surprising that the younger toddlers in Eckerman and Whatley's [1977] study depended on imitative responses.…”
Section: -Year-old Dyadscontrasting
confidence: 50%
“…The lack of redundant responses (imitative responses) differs from the work of Eckerman and Whatley [1977] and Eckerman and Stein [1982]. It is not surprising that the younger toddlers in Eckerman and Whatley's [1977] study depended on imitative responses. When the partner is unfamiliar, Eckerman and Stein [ 1982] suggest that older toddlers may continue to use imitative responses.…”
Section: -Year-old Dyadscontrasting
confidence: 50%
See 2 more Smart Citations
“…For example, we have argued that 'peers are not substitutes for infant-adult relationships, but rather are just as basic and maybe older in a phylogenetic sense and just as vital for species survival' [Lewis, Young, Brooks, & Michalson, 1975, p. 61]. Infants in the first year of life are capable of complex and positive interactions with each other [e.g., Eckerman & Whatley, 1977;Vincze, 1971]. Vandell, Wilson, and Buchanan [1980] reported that, even at 6 months of age, infant peers were able to engage in sequences where both participants acted socially, primarily by using vocalizations, touches, and smiles.…”
Section: The Role Of Peersmentioning
confidence: 99%